MOTIVASI KERJA GURU TIDAK TETAP MA AL-AZIZ DAMPIT KABUPATEN MALANG - Muhammad Amalul Yaqin; Rosichin Mansur; Arief Aridiansyah (VICRATINA, 2021)
The..teacher's role as one of the components in.teaching and.learning activities has a very decisive role in the success of learning. especially non-permanent teachers, which revolve around welfare issues and clarity of professional status, competence, and staffing. The focus of the research discusses the performance, motivation, and factors supporting and inhibiting the work of non-permanent teachers at MA Al-Aziz Dampit, Malang Regency. To achieve this goal, the researcher uses a qualitative by using a case study type of research. The researcher found that the results of this study included one sheet of certificate that the researcher had conducted research.  The work motivation of temporary teachers is to motivate non-permanent teachers when the performance of the MA Al-Aziz administration and performance in the classroom. The supporting factors of this research are adequate facilities and infrastructure. The inhibiting factor for this research is that the condition of non-permanent teachers is still in the process of extension lectures at Unira so that the delivery and teaching experience is still not optimal.